Pengembangan Lembar Kerja Peserta Didik Elektronik (e-LKPD) Larutan Elektrolit dan Nonelekrtolit berbasis Project Based Learning (PjBL) terhadap Hasil Belajar Peserta Didik kelas X SMA/MA - Rosi Efliana; Hardeli Hardeli; Alizar Alizar; Yerimadesi Yerimadesi (Postgraduate, University of Mataram, 2022)
The purpose of this research is to develop teaching materials in the form of e-SW electrolyte and nonelectrolyte solutions based on PjBL for class X SMA/MA students. The method used is the Plom Model development method with stages the Preliminary Research, Prototyping Phase, and Assessment Phase. The limitation of this research is only small group research. The assessment of this development is valid and practical. The elements that are validated are content, serving, language, and graphical components. The practical element is seen in the questionnaire conducted by 3 students and 2 teachers. The results of this study are teaching materials that meet valid and practical criteria, so they can be used for learning electrolyte and nonelectrolyte solutions for class X SMA/MA students